The F158V polymorphism in FcgammaRIIIA shows disparate associations with rheumatoid arthritis in two genetically distinct populations. - Milicic, A; Misra, R; Agrawal, S; Aggarwal, A; Brown, M; Wordsworth, B (2002)
OBJECTIVES: To investigate the association of the FcgammaRIIIA gene with rheumatoid arthritis (RA) in two genetically distinct groups: a white group from the United Kingdom and a northern Indian group. METHODS: The distributions of the two alleles of the FcgammaRIIIA F158V polymorphism were determined in 398 white patients from the United Kingdom and 63 Indian patients with RA and compared with those from 289 United Kingdom and 93 Indian healthy controls, respectively. RESULTS: Among the Indian patients, the frequency of the rare 158V allele and the proportion of 158VV homozygotes were reduced (relative risk (RR)=0.3, 95% confidence interval (95% CI) 0.1 to 1.1, p<0.06), reaching statistical significance for carrying the 158VV phenotype relative to 158FV or FF (RR=0.2, 95% CI 0.05-0.9, p<0.02). Conversely, no significant deviation in allelic frequencies was noted between the patients and controls from the United Kingdom. CONCLUSIONS: The 158VV phenotype showed a weak protective effect against developing RA in the Indian group. However, this sample was small (resulting in a low power for statistical analysis) and no independent confirmation was found in the larger white United Kingdom group. Thus the FcgammaRIIIA locus is unlikely to be of major importance in causing RA.